ACT001 Suppresses the Malignant Progression of Small‐Cell Lung Cancer by Inhibiting Lactate Production and Promoting Anti‐Tumor Immunity - Xiao‐Jing Ding; Ting Mei; Xiao‐Nan Xi; Jing‐Ya Wang; Wen‐Jing Wang; Yue Chen; Ya‐Xin Lu; Ting‐Ting Qin; Ding‐Zhi Huang (Thoracic Cancer)
ABSTRACT Background Improving the “cold” tumor immune microenvironment (TIME) of small‐cell lung cancer (SCLC) represents a promising therapeutic approach. The metabolite lactate plays a crucial role in shaping the immune‐cold tumor microenvironment (TME) and facilitating tumor progression. Phosphoglycerate kinase 1 (PGK1) is a key enzyme involved in tumor lactate metabolism. This study demonstrates that ACT001 improves the TIME of SCLC through inhibiting lactate production by targeting PGK1. Methods The cytotoxic effects of ACT001 on SCLC cell lines NCI‐H1688 and NCI‐H446 were evaluated using MTT assay, clone formation, EdU incorporation, wound healing, and invasion assays. To elucidate the mechanism of action of ACT001, proteomic techniques, pull‐down assays, LC–MS/MS, surface plasmon resonance, immunofluorescence, lactate generation, glucose uptake, and western blot assays were conducted. A xenograft model was used to assess the in vivo anti‐tumor activity of ACT001. Results ACT001 inhibited the proliferation, invasion, and metastasis of SCLC both in vitro and in vivo. Additionally, it reduced lactate accumulation and M2 macrophage polarization. Mechanistically, ACT001 released micheliolide, which covalently modified Cys316 of PGK1 under physiological conditions. This suppressed PGK1 activity and restored the distribution of PGK1 in mitochondria and the cytoplasm under hypoxic conditions. Conclusions ACT001 inhibits the malignant progression of SCLC by suppressing lactate production, modulating macrophage polarization, and restraining tumor metastasis through PGK1 targeting.